Digital Entrepreneurship Orientation as a Mediator of Social Media Exposure and Irregular Migration Intentions among Youths in Plateau State, Nigeria - Salami, Oseni; Omongbale, Roland; Ugochi, Nancy Chidiebere; Omowunmi, Kolade Olubunmi; Kwalli, Bello Muhammad; Ande, Emmanuel Zakariah (NIU Journal of Management Sciences; Vol 12 No 2 (2026): NIU Journal of Management Sciences, Vol. 12, No. 2, June 2026, 2026)
Irregular migration among Nigerian youths has emerged as a pressing concern, with many viewing migrations as a response to socio-economic challenges. This study examines how social media exposure and digital entrepreneurship orientation influence youths’ intentions to engage in irregular migration in Plateau State, Nigeria. A sample of 400 youths was selected using stratified random sampling to ensure representation across various socio-economic groups. Data were gathered through the Social Media Exposure Scale (SMES), the Digital Entrepreneurship Orientation Scale (DEOS), and the Migration Intention Scale (MIS). Four hypotheses were tested using simple linear regression, Hayes’ PROCESS model, and Pearson’s correlation at a 0.05 significance level. Findings indicate that social media exposure significantly increases migration intention (β = 0.335, t = 3.909, p < 0.05). Digital entrepreneurship orientation significantly mediated this relationship, suggesting that promoting local digital opportunities can reduce intentions to migrate (coeff. = 0.211, p < 0.05). Moreover, social media exposure was positively correlated with migration intention (r = 0.312, p < 0.05), whereas digital entrepreneurship orientation showed a significant negative correlation (r = -0.295, p < 0.05). The study concludes by recommending enhanced digital entrepreneurship education and youth-targeted programs to curb irregular migration by creating viable local opportunities. Keywords: Digital Entrepreneurship Orientation, Plateau State, Irregular Migration, Social Media Exposure, Youth, Nigeria